Parental attitudes and willingness to donate children's biospecimens for congenital heart disease research: a cross-sectional study in Shanghai, China. Issue 10 (17th October 2018) - Gao, Hongxiang; Jiang, Jun; Feng, Bei; Guo, Aihua; Hong, Haifa; Liu, Shijian
Abstract : Objectives: To assess attitudes and willingness of parents of children with congenital heart disease (CHD) regarding donating biospecimens for future CHD research, and to identify factors associated with biospecimen donation. Design: Face-to-face cross-sectional survey data were analysed using logistic regression. Setting: Cardiothoracic Surgery Inpatient Department, Shanghai Children's Medical Centre. Participants: Parents of children attending the cardiothoracic surgery inpatient department at Shanghai Children's Medical Center, 1 March–31 December 2016. Primary and secondary outcome measures: Willingness and motivation regarding donating children's biospecimens, and ethical and legal considerations concerning children's future willingness to donate. Results: Of 550 parents, 508 completed the questionnaire (response rate=92.4%). Overall, 69.1% (n=351) were willing to donate their children's biospecimens for medical research. Multivariate analysis indicated higher education level (college/graduate degree: OR 2.435, 95% CI 1.221 to 4.857, p=0.012; high school: OR 1.827, 95% CI 1.190 to 2.804, p=0.006) and children's hospitalisation history (OR 1.581; 95% CI 1.069 to 2.338, p=0.022) were positively associated with willingness to donate. The most common motivation for donation was potential benefit to other children with CHD (81.2%, n=285). The main barriers to donation were physical discomfort to their children (52.3%, n=54) and concerns about personal privacy (47.1%, n=48). Most parents (86.0%, n=302) wanted to be informed of research results using their children's donated biospecimens, and 34.8% (n=177) believed that children aged 10–18 years had the right to consent independently to research participation. Conclusions: Nearly 70% of the parents in this study were willing to donate their children's biospecimens for future CHD research. Parents' education level and children's hospitalisation history influenced willingness to donate. Most parents wanted to receive the research results related to their children's biospecimens.